2009
DOI: 10.1002/ijc.24572
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Heat‐shock pretreatment inhibits sorbitol‐induced apoptosis in K562, U937 and HeLa cells

Abstract: The aim of this study was to determine whether heat-shock pretreatment exerted a protective effect against sorbitol-induced apoptotic cell death in K562, U937 and HeLa cell lines and whether such protection was associated with a decreased cytochrome c release from mithocondria and a decreased activation of caspase-9 and -3. Following heat-shock pretreatment (42 6 0.3°C for 1 hr), these cell lines were exposed to sorbitol for 1 hr. Apoptosis was evaluated by DNA fragmentation, whereas caspase-9,-3 activation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…6A). Upon increasing incubation times with anisomycin and sorbitol there was a progressive degradation of plectin, most likely reflecting proteolysis during apoptosis (Stegh et al, 2000) induced by these compounds (Marfe et al, 2009;Liu et al, 2013). In agreement with previous reports (Raingeaud et al, 1995;Kayali et al, 2000;Bagowski et al, 2003), we observed a rapid and long lasting stimulation of ERK1/2 in HeLa cells incubated with EGF, PMA and sorbitol, whereas anisomycin was a poor stimulator of ERK1/2.…”
Section: Recombinant Ps4642 Plectin Proteins Are Not Associated With supporting
confidence: 91%
“…6A). Upon increasing incubation times with anisomycin and sorbitol there was a progressive degradation of plectin, most likely reflecting proteolysis during apoptosis (Stegh et al, 2000) induced by these compounds (Marfe et al, 2009;Liu et al, 2013). In agreement with previous reports (Raingeaud et al, 1995;Kayali et al, 2000;Bagowski et al, 2003), we observed a rapid and long lasting stimulation of ERK1/2 in HeLa cells incubated with EGF, PMA and sorbitol, whereas anisomycin was a poor stimulator of ERK1/2.…”
Section: Recombinant Ps4642 Plectin Proteins Are Not Associated With supporting
confidence: 91%
“…Since RalA-Exocyst-MAP4K4 signaling regulates NDR1 activation (Figures 3-5) and NDR1 activation is necessary for efficient apoptosis signaling [35][36][37], the role of RalA in apoptosis caused by hyperosmolarity was explored in our settings (Figure 6). High osmolarity, such as 1 M sorbitol [57], but not 0.3 M sorbitol (data not shown), promoted after 2 hours the cleavage of caspase 3 ( Figure 6A), a well established marker for on-going apoptosis. Under these conditions, NDR1 was highly phosphorylated after 30 minutes and returned to the basal level after 3 hours ( Figure 6A).…”
Section: Rala and Map4k4 Are Upstream Regulators Of Ndr1 In Stress-inmentioning
confidence: 86%
“…Previous researches have indicated that apoptosis of host cell is inhibited because of increasing SOD enzyme activity (45)(46)(47)(48). In this study, apoptosis of ANA-1 cells was evaluated by caspase-3 activity and development of apoptotic bodies by Hoechst fluorescence staining.…”
Section: Discussionmentioning
confidence: 99%